BAHASA CIREBON DIALEK PLERED DALAM KOMUNIKASI REMAJA DESA DAWUAN - muhammad kamaluddin (JIKE: Jurnal Ilmu Komunikasi Efek, 2021)
Language is used by humans to communicate in society. Both when interacting socially and cultural manifestations it has. This study examines how teenagers in Dawuan Village use the Plered language Cirebon dialect in their communication interactions. Qualitatively, this is described with a descriptive analytical approach. The language data was obtained from teenagers who communicated everyday. Through reading and notes as well as in-depth interviews, it was found that the daily lives of Cirebon-speaking Plered-speaking teenagers are motivated and influenced by several things. As for what was found as motivation and influence, namely participants, situation, education, discourse, self, environmental culture, and peers. In such a way that even though teenagers are faced with the times, the use of the Plered dialect Cirebon language is always communicative.